(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was motivated by the low proficiency of fourth-grade students at MI DDI 3 Purangi in reciting the prayers (salat), as evidenced by inaccurate pronunciation regarding articulation points (makhraj) and recitation rules (tajwid), a lack of fluency in memorization, and inconsistency in the recitation itself. The study aimed to improve students’ prayer recitation skills through the implementation of the Mimicry-Memorization method. It employed the Kemmis and McTaggart model of Classroom Action Research (CAR), conducted over two cycles, with each cycle comprising two sessions. Data were collected through recitation proficiency tests, observation, and documentation, and subsequently analyzed using descriptive quantitative methods. The results indicated that the students’ average prayer recitation proficiency improved from 69.63% in the pre-cycle stage to 85.73% in Cycle I and 94.87% in Cycle II. This improvement demonstrates that the Mimicry-Memorization method serves as a viable alternative for enhancing students’ prayer recitation skills through systematic activities involving listening, imitating, repeating, and memorizing.